2022
DOI: 10.3389/fcvm.2022.950437
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of hemodynamic parameters in aortic stenosis patients with transcatheter valve replacement by using impedance cardiography

Abstract: BackgroundThe hemodynamic changes of patients with aortic stenosis (AS) who underwent transcatheter valve replacement (TAVR) have not been completely investigated.Methods and resultsWe enrolled 74 patients with AS who underwent TAVR and assessed cardiac function changes at 1 week post-operation by impedance cardiography (ICG) in a supine position at rest for more than 15 min. Of the 74 patients, 47 had preserved left ventricular ejection fraction (LVEF ≥ 50%; preserved-LVEF group) and 27 had reduced LVEF (LVEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The decreased LV contractile and pumping performance may be due to a reduction in blood volume 5 , but another study revealed that the reduced plasma volume was offset by the increase in erythrocyte volume 30 . LVET, PEP, and STR are three clinical indicators that serve as effective screening tools for left ventricular diastolic dysfunction more than systolic dysfunction 32 . The increased STR may be due to the decreased velocity of myocardial fiber shortening during the ejection period 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The decreased LV contractile and pumping performance may be due to a reduction in blood volume 5 , but another study revealed that the reduced plasma volume was offset by the increase in erythrocyte volume 30 . LVET, PEP, and STR are three clinical indicators that serve as effective screening tools for left ventricular diastolic dysfunction more than systolic dysfunction 32 . The increased STR may be due to the decreased velocity of myocardial fiber shortening during the ejection period 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Volume overload could cause stretching of the atria and lead to atrial remodelling, potentially creating a substrate of AF 47 . Although prior reports have suggested that preload may be improved after TAVI, 48 volume overload at baseline is strongly associated with HF hospitalization and all‐cause death, 49 suggesting that fluid overload may be persistent in some patients even after valve replacement. Nevertheless, further investigation is needed to explore whether decongestive treatments in overhydrated AS patients could prevent new‐onset AF and further improve outcomes beyond TAVI.…”
Section: Clinical Factors Associated With Heart Failure Hospitalizati...mentioning
confidence: 99%